Academic Moral in Psychiatry or Pedagogical Psychiatry - Osman Ozdemir (Psikiyatride Güncel Yaklaşımlar)
Significant differences can be observed among generations due to changes in their upbringing styles, socioal and economic conditions. It may be mentioned a new generation questioning the authority and rebel against them. They are also wiser than previous generation accepting unquestioningly the authority. They are more submissive and abstemious. The academic values accepting absolutely true will be discussed as a result of personal and social changes. In this commentary academic moral of new generation in psychiatry was focused in the context of critical pedagogy. [Psikiyatride Guncel Yaklasimlar - Current Approaches in Psychiatry 2016; 8(3.000): 303-308]